Effect of glycemic gap on prognosis and complications in vulnerable period of acute heart failure: Glycemic Gap’s Impact on Acute Heart Failure Prognosis - Zheng, Lin; Zheng, Weifeng; Zhang, Mingming; Li, Bo (Journal of Medical Biochemistry, 2024)
Background: To investigate the effect of glycemic gap on the prognosis and complications of heart failure in patients with acute heart failure. Methods: 100 patients with acute heart failure treated in our hospital from January 2022 to August 2023 were divided into two groups according to the prognosis: good prognosis group (n = 58) and poor prognosis group (n = 42). Univariate analysis of the prognostic factors of acute heart failure patients in vulnerable period, multivariate Logistics regression analysis of the prognostic factors of acute heart failure patients. ROC analysis of the value of glycemic gap in predicting the prognosis of patients with acute heart failure in the vulnerable period of heart failure, and compare the occurrence of complications between the two groups. Including: arrhythmia, angina pectoris, cardiogenic shock, thrombosis. Results: There was no significant difference in age, sex, history of hypertension, BMI, TG, history of diabetes and serum potassium between the two groups. The glycemic gap, BNP, Ang II, cTnI and SCR in the good prognosis group were lower than those in the poor prognosis group, while LVEF and hemoglobin were higher than those in the poor prognosis group. Binary Logistics regression analysis showed that. Glycemic gap, BNP, Ang II, cTnI, SCR, LVEF and hemoglobin were independent prognostic factors in patients with acute heart failure. The area under the glycemic gap value curve was determined to be 0.8071. The sensitivity of the assessment was 72.8, while the specificity was 70.5, . The incidence of complications in the good prognosis group (1.72%) was significantly lower than that in the poor prognosis group (16.67%). Conclusions: Glycemic gap is related to the prognosis and complications of heart failure in patients with acute heart failure. Hyperglycemia gap will affect the prognosis of heart failure in patients with acute heart failure, resulting in poor prognosis and increasing the incidence of complications.